2019
DOI: 10.35940/ijrte.c5248.098319
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Descriptive Writing Learning Model using the Audio Visual Media

Abstract: This development research aims to develop a learning model that has been used by teachers to become a new learning model that is able to create a learning process that is fun, no burden, and not boring. The research procedure follows the 4-D development phase (four D) Thiagarajan namely: (1) defining; (2) design; (3) development; (4) distribution. The product trial was carried out on two high school and city school category categories (high level) established Padangpanjang SMPN 1 and low-level and peripheral g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The findings of this study relate with those of the study by Novelti, Kristiawan and Erpidawati [20] about the development of the descriptive writing learning model using audio-visual media. It was found in this study that teachers used the learning model as a new learning model that can create a learning process that is fun, not burdensome and boring.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The findings of this study relate with those of the study by Novelti, Kristiawan and Erpidawati [20] about the development of the descriptive writing learning model using audio-visual media. It was found in this study that teachers used the learning model as a new learning model that can create a learning process that is fun, not burdensome and boring.…”
Section: Discussionsupporting
confidence: 84%
“…In Malaysia, the study by Veramuthu and Shah [35] use a collaborative approach in teaching and learning descriptive writing, and it is received as one of its approach which aids English Second Language (ESL) learners to be proficient in writing. Furthermore, the study by Novelti, Kristiawan and Erpidawati [20] developed a descriptive writing model through audio-visual in Indonesia, and it supports students in improving descriptive writing ability. A study conducted by Ikwuka and Samuel [13] in Nigeria revealed that digital lesson contents improved students' achievement in chemistry subject.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have clearly shown that students become able to produce longer texts when they get engaged in technological educational environments than texts which are produced by hand. In addition, students have opportunities to revise what they write frequently (Novelti et al, 2019;Kristiawan, 2014). Hence, the quality of their writing becomes better (Zawitinski, 2012).…”
Section: Marlenimentioning
confidence: 99%
“…Writing activities involve several factors, including the writer as the message's delivery, the writing's content, the channel or media, and the reader (Nisja, 2019). Teachers, on the other hand, can assess the objectives provided, identify strengths and weaknesses, and devise new strategies to improve the learning process and writing skills (Novelti et al, 2019). Furthermore, students can improve their writing skills if they are accompanied by a learning process and practice (Wilda & Wahidah, 2021).…”
Section: Introductionmentioning
confidence: 99%